INOVASI PENGOLAHAN SERAI MENJADI MINYAK ATSIRI BERNILAI EKONOMI TINGGI MELALUI METODE DESTILASI UAP SEDERHANA - Vidiyastutik, Elok Dwi; Nazilah, Vita Rahmatun; Jannah, Amalia Hikmatul; Mustofa, Ahmad; Hidayat, Ibnu (Abdi Panca Marga, 2024)
This service aims to examine the effectiveness of a simple steam distillation method in processing lemongrass into essential oil with high economic value. The simple steam distillation method is a technique for separating a mixture of substances based on their boiling point differences, using steam as the separation medium. The simple steam distillation method is chosen for its simplicity, low cost, and ability to produce essential oils of good quality. The process begins with the preparation of fresh lemongrass raw materials, followed by the distillation process using a specially designed steam distillation apparatus. The variables being observed include distillation time, the ratio of raw materials to water, and temperature. The results of the service show that this method is effective in extracting essential oils with adequate yield and high quality. Chemical analysis of the essential oil produced shows the presence of main components such as citronella, geraniol, and limonene, which have a high market value. This service provides important insights into the potential economic value of citronella essential oil and offers alternative processes that can be applied on a small industrial scale. Thus, simple steam distillation has proven to be an efficient and economical method for processing lemongrass into high-value products.